Influence of Human Cytomegalovirus Glycoprotein O Polymorphism on the Inhibitory Effect of Soluble Forms of Trimer- and Pentamer-Specific Entry Receptors - Brait, Nadja (J Virol, 2020)
Human cytomegalovirus (HCMV) envelope glycoprotein complexes, gH/gL/gO trimer and gH/gL/UL128-131 pentamer, are important for cell-free HCMV entry. While soluble NRP2-Fc (sNRP2-Fc) interferes with epithelial/endothelial cell entry through UL128, soluble platelet-derived growth factor receptor α-Fc (sPDGFRα-Fc) interacts with gO, thereby inhibiting infection of all cell types. Since gO is the most variable subunit, we investigated the influence of gO polymorphism on the inhibitory capacities of sPDGFRα-Fc and sNRP2-Fc. Accordingly, gO genotype 1c (GT1c) sequence was fully or partially replaced by gO GT2b, GT3, and GT5 sequences in the bacterial artificial chromosome (BAC) TB40-BAC4-luc background (where luc is luciferase). All mutants were tested for fibroblast and epithelial cell infectivity, for virion content of gB, gH, and gO, and for infection inhibition by sPDGFRα-Fc and sNRP2-Fc. Full-length and partial gO GT swapping may increase epithelial-to-fibroblast ratios due to subtle alterations in fibroblast and/or epithelial infectivity but without substantial changes in gB and gH levels in mutant virions. All gO GT mutants except recombinant gO GT1c/3 displayed a nearly complete inhibition at 1.25 μg/ml sPDGFRα-Fc on epithelial cells (98% versus 91%), and all experienced complete inhibition on fibroblasts (≥99%). While gO GT replacement did not influence sNRP2-Fc inhibition at 1.25 μg/ml on epithelial cells (97% to 99%), it rendered recombinant mutant GT1c/3 moderately accessible to fibroblast inhibition (40%). In contrast to the steep sPDGFRα-Fc inhibition curves (slope of >1.0), sNRP2-Fc dose-response curves on epithelial cells displayed slopes of ∼1.0, suggesting functional differences between these entry inhibitors. Our findings demonstrate that artificially generated gO recombinants rather than the major gO genotypic forms may affect the inhibitory capacities of sPDGFRα and sNRP2 in a cell type-dependent manner. IMPORTANCE Human cytomegalovirus (HCMV) is known for its broad cell tropism, as reflected by the different organs and tissues affected by HCMV infection. Hence, inhibition of HCMV entry into distinct cell types could be considered a promising therapeutic option to limit cell-free HCMV infection. Soluble forms of cellular entry receptor PDGFRα rather than those of entry receptor neuropilin-2 inhibit infection of multiple cell types. sPDGFRα specifically interacts with gO of the trimeric gH/gL/gO envelope glycoprotein complex. HCMV strains may differ with respect to the amounts of trimer in virions and the highly polymorphic gO sequence. In this study, we show that the major gO genotypes of HCMV that are also found in vivo are similarly well inhibited by sPDGFRα. Novel gO genotypic forms potentially emerging through recombination, however, may evade sPDGFRα inhibition on epithelial cells. These findings provide useful additional information for the future development of anti-HCMV therapeutic compounds based on sPDGFRα.